2010
DOI: 10.1007/s12274-010-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of catalyst-free and catalyst-induced GaN nanowires

Abstract: GaN nanowires have been grown by molecular beam epitaxy either catalyst-free or catalyst-induced by means of Ni seeds. Under identical growth conditions of temperature and Ⅴ/Ⅲ ratio, both types of GaN nanowires are of wurtzite structure elongated in the Ga-polar direction and are constricted by M-plane facets. However, the catalyst-induced nanowires contain many more basal-plane stacking faults and their photoluminescence is weaker. These differences can be explained as effects of the catalyst Ni seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
119
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 49 publications
(67 reference statements)
5
119
0
Order By: Relevance
“…21 They found that by using Ni as catalyst, more basal-plane stacking faults can be observed (shown in Fig. 3).…”
Section: Self-organized Growth Of Gan Nanorodsmentioning
confidence: 97%
See 3 more Smart Citations
“…21 They found that by using Ni as catalyst, more basal-plane stacking faults can be observed (shown in Fig. 3).…”
Section: Self-organized Growth Of Gan Nanorodsmentioning
confidence: 97%
“…They suggested four possible explanations for the occurrence of the stacking faults which are all related to the presence of the catalyst at the nanorod tip where growth takes place. 21 Firstly, the binding configuration of the GaN nucleus at the NW-catalyst interface might adopt the zinc-blende (ZB) configuration of the cubic solid NiGa mixture. Secondly, the Ni catalyst could be incorporated to some extent, which could stabilize the ZB structure.…”
Section: Self-organized Growth Of Gan Nanorodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ni for the case of InN nanowires). For GaN nanowires, this has been discussed for example by Cheze et al [1]. In this context we would like to stress again, that the optical properties discussed in the paper refer to catalyst-free InN nanowires.…”
mentioning
confidence: 63%